PARADISE LOST - MILTON, JOHN (Collier Books New York, 1966)
Satan and his fellow rebel angels contemplate on corrupting God's beloved new creation, Mankind. He volunteers and prepares to leave. His children - Sin and Death - build a bridge between Hell and Earth. And disguising himself as a cherub, he lands on Earth.
Keywords: English Literature; English Fiction; General Reading